PERAN KOPERASI MERAH PUTIH SEBAGAI OFFTAKER PRODUK PERTANIAN LOKAL UNTUK STABILISASI HARGA - Nuroni, Ahmad; Ahmadi, Ahmadi; Novaria, Eva (ACADEMIA: Jurnal Inovasi Riset Akademik, 2026)
Agricultural commodity price volatility is a persistent structural problem in Indonesia, often detrimental to farmers due to the dominance of middlemen and long distribution chains. This study focuses on analyzing the effectiveness of the Red and White Village/Sub-district Cooperative (KMP) program as an institutional solution that acts as an offtaker or standby buyer to stabilize prices at the producer level. Using a descriptive qualitative approach through a study of pilot project evaluation documents in West Java and an analysis of supply chain management literature, this study examines the mechanisms of planting contracts, stock management, and financing facilitation. The study findings indicate that the KMP intervention significantly reduced the supply chain from 5–7 layers to 2–3 layers, which directly impacted the selling price at the farm level by 10–20% compared to the free market price during the main harvest. The forward contract mechanism proved effective in providing certainty of market absorption and transferring price risk from farmers to the cooperative. It concluded that KMP plays a vital role in transforming the agricultural ecosystem and controlling food inflation, but the sustainability of this model is highly dependent on support for access to affordable capital and the integration of digital technology for operational efficiency. ABSTRAK Volatilitas harga komoditas pertanian menjadi masalah struktural yang persisten di Indonesia, sering kali merugikan petani akibat dominasi tengkulak dan panjangnya rantai distribusi. Penelitian ini berfokus pada analisis efektivitas program Koperasi Desa/Kelurahan Merah Putih (KMP) sebagai solusi kelembagaan yang berperan sebagai offtaker atau pembeli siaga guna menstabilkan harga di tingkat produsen. Dengan menggunakan pendekatan kualitatif deskriptif melalui studi dokumen evaluasi pilot project di Jawa Barat serta analisis literatur manajemen rantai pasok, penelitian ini menelaah mekanisme kontrak tanam, pengelolaan stok, dan fasilitasi pembiayaan. Temuan studi menunjukkan bahwa intervensi KMP mampu memangkas rantai pasok secara signifikan dari 5–7 lapis menjadi 2–3 lapis, yang berdampak langsung pada peningkatan harga jual di tingkat petani sebesar 10–20% dibandingkan harga pasar bebas saat panen raya. Mekanisme forward contract terbukti efektif dalam memberikan kepastian serapan pasar dan mentransfer risiko harga dari petani kepada koperasi. Disimpulkan bahwa KMP memiliki peran vital dalam mentransformasi ekosistem pertanian dan mengendalikan inflasi pangan, namun keberlanjutan model ini sangat bergantung pada dukungan akses permodalan murah serta integrasi teknologi digital untuk efisiensi operasional.